2002
DOI: 10.1016/s1470-0328(02)01311-3
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence spectroscopy for the diagnosis of cervical intraepithelial neoplasia

Abstract: Objective To assess the feasibility of autofluorescence spectroscopy in the diagnosis of cervical intraepithelial neoplasia (CIN) using broadband light excitation. Design Feasibility study.Setting Colposcopy clinic of an university hospital.Population Sixty-eight patients at risk for CIN.Methods After excitation with a broadband light between 375 and 440 nm, spectral distribution of native tissue fluorescence (autofluorescence) was acquired from 685 cervical sites for the localisation and differentiation of CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…As found also by Chia, Teck-Chee et al [9], and Weingandt et al [10], we have demonstrated that intestinal tissues can be photobleached by blue light at high enough radiant exposure such as 50-80 J/cm 2 . A number of fluorophores, including collagen, elastin, NADH, and FAD [7] are present in colon.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As found also by Chia, Teck-Chee et al [9], and Weingandt et al [10], we have demonstrated that intestinal tissues can be photobleached by blue light at high enough radiant exposure such as 50-80 J/cm 2 . A number of fluorophores, including collagen, elastin, NADH, and FAD [7] are present in colon.…”
Section: Discussionsupporting
confidence: 88%
“…Secondly, photobleaching implies a degree of biochemical alteration of the tissue and so, in principle, could have adverse biological effects that might limit the useable exposure to ensure safety [3]. In imaging intraepithelial neoplasia in the cervix, Weingandt et al [10] found no significant photobleaching after 5 minutes exposures to a filtered short-arc xenon lamp with an output power of 200 mW at 375-440 nm (D-Light, Karl Storz, Tuttlingen, Germany). However, significant photobleaching ( > 10%) of endogenous fluorophores, including collagen, was observed in colon ex vivo for surface radiant exposures of 10-15 J cm À2 at 458 nm [9].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a study of 146 patients comparing 18 different excitation wavelengths found that three broad ranges of excitation - 330-340 nm (UV), 350-380 nm (UV) and 400-450 nm (blue) excitation – gave best sensitivity and specificity for detection of high grade precancer58. Across all studies, fluorescence intensity of precancerous lesions is lower than that of normal squamous tissue, and the peak emission wavelength of precancers is shifted to longer emission wavelengths relative to that of normal tissue56-59. The decreased fluorescence intensity has been attributed to the decreased stromal fluorescence and increased stromal absorption of cervical precancers60-62, while the spectral shift is attributed to both increased hemoglobin absorption and increased mitochondrial fluorescence in precancers60-62.…”
Section: In Vivo Optical Imaging Technologiesmentioning
confidence: 95%
“…Importantly, Weingandt noted that inflammatory lesions may give rise to false positive fluorescence measurements59, and recent studies in other organ sites indicate that inflammation and precancer both exhibit a similar loss in stromal autofluorescence65. Techniques which better probe changes in epithelial signatures, such as depth-resolved spectroscopy54 or high resolution imaging29, 66, may give rise to better specificity.…”
Section: In Vivo Optical Imaging Technologiesmentioning
confidence: 99%
“…However, most pure optical imaging technologies either utilize the back scattered ballistic photons [12][13][14][15][16][17], or rely on the nonlinear optical phenomenon [18,19]. Due to the high scattering of the biological tissue, the penetration depth is generally limited to the most superficial epithelial layers for these methods [4].…”
Section: Introductionmentioning
confidence: 99%